Spectrophotometric study determining staining tendency in different restorative materials (longitudinal in vitro study) - Ghada Alhamed; Salsabil Massoud; Mazen Doumani (Elsevier, 2021)
Aim: Our aim was to measure the discolouration degrees in a packable composite, zircon, ceramic, a flowable composite, and GIC (glass isomer cement) and to determine their tendencies to discolour to provide guidance to dentists and prosthodontist for choosing proper materials for cases in which aesthetics is the main treatment goal. Materials and methods: Sixty discs were fabricated from the composite, zircon, ceramic, the flowable composite, and GIC, and natural teeth were the control group. The shades were recorded using the Ivoclar Vivadent Shade Guide, and readings were recorded from a Vita Easyshade 4.0 spectrophotometer before immersion, after 1 week, 2 weeks, 3 weeks, and 24 weeks of immersion in coffee. The analysis was performed using a SPSS paired t-test and CIE 76 formula. Results: The ceramic had a starting shade of B1 and kept the same colour throughout the testing period. Zircon had a starting shade of A3 and transitioned to B3 by the second week. The composite had a shade of A1, and after the first week, it was A4; in the second week and afterwards, it was C4. The flowable composite had a starting shade of A1, and after one week, the shade was B3, and then after one more week A3.5; after five months, it was A4. Conclusion: The ceramic showed no change, making it ideal for aesthetic regions and anterior replacements. Zircon had the second-highest colour stability, whereas all the other materials showed variable degrees of colour and surface changes, making them not ideal choices for anterior restorations. Thus, this information can aid choices for aesthetic regions to provide the highest longevity.